Invasive pulmonary infection caused by Chrysosporium articulatum: the first case report. Issue 1 (4th November 2014) - Suankratay, Chusana; Dhissayakamol, Onwalee; Uaprasert, Noppacharn; Chindamporn, Ariya
Summary Chrysosporium species, saprobic soil fungi, comprise more than 60 species. There is some confusion regarding the taxonomy and nomenclature between Chrysosporium and Emmonsia since the causative agents of adiaspiromycosis, the development of big thick‐walled spores (adiaspores) in humans or animals, were previously thought to be Chrysosporium. Chrysosporium articulatum has never been reported to cause invasive infection in humans. We report herein the first case of invasive pulmonary infection caused by Chrysosporium articulatum in a 16‐year‐old man with acute T‐cell lymphoblastic leukaemia. He was successfully treated with voriconazole.